Effect of Combination Therapy of Canagliflozin Added to Teneligliptin Monotherapy in Japanese Subjects with Type 2 Diabetes Mellitus: A Retrospective Study - Yoshiro Fushimi; Atsushi Obata; Junpei Sanada; Yuichiro Iwamoto; Akiko Mashiko; Megumi Horiya; Akiko Mizoguchi-Tomita; Momoyo Nishioka; Yuki Kan; Tomoe Kinoshita; Seizo Okauchi; Hidenori Hirukawa; et al. (Journal of Diabetes Research)
Recently, dipeptidyl peptidase-4 (DPP-4) inhibitors and sodium-glucose cotransporter 2 (SGLT2) inhibitors have been very often used in subjects with type 2 diabetes mellitus (T2DM). In addition, combination drugs of both inhibitors have attracted much attention in aspects of its cost-effectiveness and improvement of patients’ adherence. However, it is still poorly understood which factors are related to the efficacy of SGLT2 inhibitors as add-on therapy to DPP-4 inhibitors. Therefore, we aimed to elucidate in which type of individuals and/or under which conditions canagliflozin as add-on therapy to teneligliptin could exert more beneficial effects on glycemic control and/or renal protection. We retrospectively analyzed 56 Japanese subjects with T2DM in the real-world clinical practice. Three months after starting the combination therapy, the change of HbA1c (ΔHbA1c) was strongly related to HbA1c levels at baseline. As expected, serum glucagon level was increased after starting the combination therapy. Interestingly, however, the change of glucagon levels (Δglucagon) was not related to HbA1c levels at baseline, ΔHbA1c, and other parameters, which indicated that the increase of glucagon did not clinically affect the effectiveness of combination therapy. In addition, the change of urinary albumin excretion (ΔUAE) was negatively correlated with systolic blood pressure and HbA1c levels at baseline and positively correlated with the change of systolic blood pressure (ΔsBP) in univariate analysis. Furthermore, in multivariate analysis, only ΔsBP was the independent factor associated with ΔUAE. Taken together, canagliflozin as add-on therapy to teneligliptin improves glycemic control in a Δglucagon-independent manner and reduces UAE in a ΔsBP-dependent manner in Japanese subjects with T2DM.